Detergent‐insoluble inclusion constitutes the first pathology in PFN1 transgenic rats. Issue 4 (12th August 2020) - Yuan, Guixiu; Cui, Shiquan; Chen, Xuan; Song, Haochang; Huang, Cao; Tong, Jianbin; Yuan, Zhentin; Yu, Lin; Xiong, Xinrui; Zhao, Jihe; Huang, Bo; Wu, Qinxue; et al.
Abstract: Mutation of profilin 1 ( PFN1 ) can cause amyotrophic lateral sclerosis (ALS). To assess how PFN1 mutation causes the disease, we created transgenic rats with human genomic DNA that harbors both the coding and the regulatory sequences of the human PFN1 gene. Selected transgenic lines expressed human PFN1 with or without the pathogenic mutation C71G at a moderate and a comparable level and in the similar pattern of spatial and temporal expression to rat endogenous PFN1. The artificial effects of arbitrary transgene expression commonly observed in cDNA transgenic animals were minimized in PFN1 transgenic rats. Expression of the mutant, but not the wild type, human PFN1 in rats recapitulated the cardinal features of ALS including the progressive loss of motor neurons and the subsequent denervation atrophy of skeletal muscles. Detergent‐insoluble PFN1 inclusions were detected as the first pathology in otherwise asymptomatic transgenic rats expressing mutant human PFN1. The findings suggest that protein aggregation is involved in the neurodegeneration of ALS associated with PFN1 mutation. The resulting rat model is useful to mechanistic study on the ALS. Abstract : Pathogenic mutation of PFN1, an actin‐binding protein, causes motor neuron degeneration in amyotrophic lateral sclerosis. Transgenic rats expressing a mutant, but not the wild type, PFN1 recapitulated the cardinal features of the disease including late‐onset motor neuron degeneration and denervation atrophy. Prior to neurodegeneration in the transgenic rats, protein aggregation was detected as the first pathology. Mutant PFN1 aggressively formed detergent‐insoluble inclusions in affected motor neurons as detected by both biochemical analysis and pathological assays. The data suggest protein aggregation as an active player in the disease pathogenesis.